2016
DOI: 10.1021/acs.energyfuels.5b02180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emulsified Water on Asphaltene Instability in Crude Oils

Abstract: Understanding asphaltene precipitation and subsequent deposition during oil production is of great importance for the oil industry nowadays because of the potential risk associated with this heavy fraction in plugging wellbores and production equipment. Although water is commonly present in the produced fluids, because of instrument limitations and inadequate techniques, it is usually separated from the oil prior to any experimental analysis. Therefore, the effect of water on asphaltene stability and depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 35 publications
(80 reference statements)
6
47
0
Order By: Relevance
“…In the past decade, a limited number of controversial research studies have been undertaken to understand the effect of water emulsions on asphaltene precipitation and deposition. From a review of available literature 2831 , it appears that opinion differs significantly as to which experimental methods should be utilised to determine the asphaltene stability and deposition tendency, which conditions should be applied and how data should be interpreted. Several workers have claimed that the existence of water microemulsions had no remarkable influence on the asphaltene precipitation 28,31 , while others concluded that water increases the solubility of the asphaltenes in the system and delays the asphaltene aggregation and deposition phenomena 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a limited number of controversial research studies have been undertaken to understand the effect of water emulsions on asphaltene precipitation and deposition. From a review of available literature 2831 , it appears that opinion differs significantly as to which experimental methods should be utilised to determine the asphaltene stability and deposition tendency, which conditions should be applied and how data should be interpreted. Several workers have claimed that the existence of water microemulsions had no remarkable influence on the asphaltene precipitation 28,31 , while others concluded that water increases the solubility of the asphaltenes in the system and delays the asphaltene aggregation and deposition phenomena 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, asphaltenes are known to be surface-active and assemble at oil-water and air-water interfaces, often forming an interfacial film. This leads to flow assurance problems, such as difficulty in transporting highly viscous fluids or separating phases in stabilized water-in-oil emulsions [13,14]. Furthermore, tailings/wastewater containing bitumen and crude oil that are discharged into tailing ponds often deposit and form a film on the pond [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…More studies are anticipated in the future for better clarifications of this mechanism. While investigation of asphaltene-brine interaction is still ongoing, some studies were made with dissimilar opinions, whereby some researchers advocated that the presence of water microemulsions has no significant effect on the precipitation and deposition of the asphaltene [24,25], whereas the others recommended that asphaltene deposition and aggregation were observed to reluctantly act in the presence of water, and also that the asphaltenes solubility was equally found to have increased when water was present [26,27].…”
Section: Introductionmentioning
confidence: 99%